Synthesis of Poly Lactic Acid from Lactic Acid Using Direct Polycondensation Method Using Al(DS)3 and AlCl3 Catalysts - Aziz, Ahmad Musonnifin; Widjaja, Tri; Ni’mah, Hikmatun (2477 - 6165, 2024)
Poly Lactic Acid (PLA) is a type of polymer that is widely researched because it can meet the requirements for biodegradable polymers and can be used in several of applications. Making PLA using the direct polycondensation method is carried out in 3 process stages, namely dehydration, polycondensation and recrystallization. Dehydration was carried out at 130℃ for 1 hour. Polycondensation was carried out at varying temperatures of 160℃, 180℃ and 200℃ with a concentration of 0.15% for 6 hours. In the meantime, 50 ml of methanol was added, and vacuum conditions were used to carry out the recrystallization process. After that, the viscosity method was used to determine PLA's molecular weight. The highest molecular weight and other properties of PLA, such as its functional groups and thermal behavior, are the aim of this study. The findings of the study indicate that PLA has its maximum molecular weight at 180°C, where it is 15576 gr/mol for PLA+Al(DS)3 and 10771 gr/mol for PLA+AlCl3. The PLA+Al(DS)3 and PLA+AlCl3 spectra display the same bands in the stretching and bending vibration modes, according to the FTIR test. Meanwhile, in the TGA analysis, the highest decomposition was shown by PLA+Al(DS)3 at a temperature of 365℃.